Improving customer experience in the cruise industry in the post pandemic era - Panagiotis Manolitzas; Niki Glaveli; Stergios Palamas; Evangelos Grigoroudis; Constantin Zopounidis (Cogent Business & Management, 2022)
The current research re-examines cruisers' satisfaction in the context of online user generated content extracted from CruiseCritics through the application of Multicriteria Satisfaction Analysis Method (MUSA). MCDA methods evaluate alternative courses of action with respect to criteria that reflect the main dimensions of the decision-making problem, involving human judgment and preferences. More precisely, the present work illustrates an evidence-based decision-making approach in the areas of quality management and cruisers' satisfaction and reveals valuable information to the decision-makers like global satisfaction indices, criteria weights and action diagrams to assist them restart and improve the performance of the cruise industry at the post pandemic era. Specifically, the analysis elucidated that the cruise industry players should reconsider the "value for money" aspect of their offering, continue investing in areas of service quality like cabins, service, and dining and closely monitor the fitness recreation, entertainment, and enrichment aspects of the cruisers' experience.
Keywords: 650; cruise critics; cruise industry; cruiser satisfaction; decision making; MCDA/ MUSA